2019
DOI: 10.1007/s00520-018-4633-z
|View full text |Cite
|
Sign up to set email alerts
|

Problems sleeping with prostate cancer: exploring possible risk factors for sleep disturbance in a population-based sample of survivors

Abstract: Problems sleeping with prostate cancer: exploring possible risk factors for sleep disturbance in a population-based sample of survivors. Supportive Care in Cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Further, SDs are common as a post-treatment complication [ 59 ]. Finally, night shift work has been demonstrated to be positively associated with the PCa incidence [ 60 ].…”
Section: Modifiable (Preventable) Risk Factorsmentioning
confidence: 99%
“…Further, SDs are common as a post-treatment complication [ 59 ]. Finally, night shift work has been demonstrated to be positively associated with the PCa incidence [ 60 ].…”
Section: Modifiable (Preventable) Risk Factorsmentioning
confidence: 99%
“…It is possible that men experience discomfort due to diarrhoea or constipation and, as for urinary incontinence, may worry about leakage and embarrassment from wearing bowel incontinence pads. As well as the adverse psychological and physical effects, these physical symptoms may cause sleep disturbance [41]; sleep disorders, in turn, are linked with cancer-related fatigue [42]. Thus, the constellation of consequences of these post-treatment symptoms may explain their association with the pain-fatiguedepression symptom cluster.…”
Section: Factors Associated With the Symptom Clustermentioning
confidence: 99%
“…Therefore, there is an urgent need for healthcare personnel to provide related diagnosis and treatment, as well as prognostic management and services to reduce sleep disorders in cancer survivors. 24 The average sleep time of the patients in this study was approximately 6.87 h after treatment. Although most of the patients also claimed to have good sleep quality, a detailed analysis of the data showed that 34.8% of the patients did not fall asleep within 30 min, more than three times in the month before treatment, while only 17.4% remained affected after treatment, representing a 50% improvement.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, there is an urgent need for healthcare personnel to provide related diagnosis and treatment, as well as prognostic management and services to reduce sleep disorders in cancer survivors. 24 …”
Section: Discussionmentioning
confidence: 99%